Thermal and size effect on the R lines luminescence in YAG:Cr3+ - ERDEM, MURAT; YAHŞİ, UĞUR (ELSEVIER SCIENCE BV, 2015)
We have studied the line positions and widths of R lines luminescence of nanopowder samples of Y3Al5O12: Cr (3+) particles with diameters ranging from about 28 to 250 nm. For each sample we have measured accurately the emission spectrum from 30 K to 300 K. The spectra generally consisted of the R-lines narrow spectral emission and of the accompanying vibronic side-bands. From larger to shorter diameters of powders at each temperature we noticed an increase of the width at half-maxima of the R lines luminescence. The emissions were shifted towards lower energies when increasing the temperature from 30 K to 300 K. The temperature dependent broadening and shift of the R lines in the different samples can be accounted for by adjusting the electron-phonon parameters in the formulas describing these processes and using the same Debye temperature of the bulk material. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Vibronic side-bands; Line shift; Line broadening; Nanocrystals; TEMPERATURE-DEPENDENCE; CHROMIUM IONS; YAG; SPECTRA; FLUORESCENCE; NANOCRYSTALS; CRYSTALS; CR3+